Cytosystematics, sex chromosome translocations and speciation in African mole-rats (Bathyergidae: Rodentia) - Deuve, Jane Lynda (Stellenbosch : University of Stellenbosch, 2008)
Thesis (PhD (Botany and Zoology))--University of Stellenbosch, 2008.